2019
DOI: 10.1088/1755-1315/354/1/012129
|View full text |Cite
|
Sign up to set email alerts
|

An Inquisition of Envelope Fabric for Building Energy Performance Using Prominent BIM-BPS Tools—A Case Study in Sub-Tropical Climate

Abstract: Energy efficient building is enhancing a worldwide movement as a policy to lessen the carbon footprint. With the intention of zero energy building in sub-tropical climates, exertion should be placed to minimize the overall energy usage to the greatest scope by incorporating apposite construction skills into the whole design process. Suitable building envelope resources is one of the most effective ways to manage energy flows, minimize energy loss, and maintain a comfortable environment for occupants. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
1
0
3
Order By: Relevance
“…A fachada, também caraterizada como envelope do edifício, costuma ser alvo de retrofit pois ela precisa ser adequada para atingir um desempenho superior já que está susceptível à luz, calor, ar e outros impactos (UDDIN et al, 2019). Yasar e Kalfa (2012) e Smith, Isaacs, Burgess e Cox (2012) apud Spiegelhalter et al (2014) apresentam que a alternativa mais comum de retrofit é a troca de vidros da fachada por vidros low-e 3 .…”
Section: O Que é Retrofitunclassified
See 2 more Smart Citations
“…A fachada, também caraterizada como envelope do edifício, costuma ser alvo de retrofit pois ela precisa ser adequada para atingir um desempenho superior já que está susceptível à luz, calor, ar e outros impactos (UDDIN et al, 2019). Yasar e Kalfa (2012) e Smith, Isaacs, Burgess e Cox (2012) apud Spiegelhalter et al (2014) apresentam que a alternativa mais comum de retrofit é a troca de vidros da fachada por vidros low-e 3 .…”
Section: O Que é Retrofitunclassified
“…Algumas pesquisas utilizam na simulação um padrão genérico de período de uso e operação do edifício de acordo com a tipologia da edificação. Por isso que uma das causas comuns de erro das Simulações de Desempenho de Edifícios (Building Performance Simulation -BPS) é a informação sobre o comportamento das pessoas e quanto ao período de operação do edifício (UDDIN et al, 2019). Neste caso entrevista com os usuários do edifício contribuem com uma identificação mais completa (ASHRAE apud COULTER; DUBLER; LEICHT, 2013).…”
Section: Padrão Do Consumounclassified
See 1 more Smart Citation
“…Kamaruzzaman et al [32], for example, identified key sustainability criteria set by various energy certification schemes, such as, for example, LEED, BREEAM, GREEN MARK, GBI, etc. Di Bari et al [33][34][35] investigated the ways of reducing environmental impacts and improving the overall performance of building concurrently with reducing the overall cost of operation and maintenance of buildings. They have found that this can be done by adopting the BIM-integrated LCA approach.…”
Section: Bim Application For Building Energy Assessmentmentioning
confidence: 99%
“…The passive approaches, however, harness the internal environment conditions by taking advantage of the building design items, such as layout and form, rather than mechanical systems. The passive energy-saving solutions maximize the use of environmental sources, such as heating, cooling, ventilation, and lighting to create a comfortably built environment with a minimized energy demand [14][15][16]. Building envelop design can affect 20-60% of the building energy input, making it crucial for high-performance, sustainable buildings [17].…”
Section: Introductionmentioning
confidence: 99%